Lifelong Educational and Decolonization Programs for the Batwa Indigenous People of Southwestern Uganda - Sekiwu, Denis; Adyanga, Francis Akena; Genza, Gyaviira Musoke; Rugambwa, Nina Olivia; Muwagga, Anthony Mugagga (East African Journal of Interdisciplinary Studies, 2024)
This article is based on a study conducted among the Batwa Indigenous people in southwestern Uganda between 2021 and 2022. The study aimed to explore culturally relevant lifelong education and decolonization programs for the Batwa people. Using indigenous research methodology, 60 participants comprising of elders, parents, children and teachers were recruited from the Batwa community for the study. We used Egalitarian liberalism and justice in education (ELJE) theory as analytical framework. Key findings demonstrate that participants were conscious of the challenges faced by their community and collectively brainstormed practical redress measures. These measures include but are not limited to setting up an entrepreneurship education program, vocational and skilling programs, and promotion of Rutwa language. Besides, some specific Batwa life skills identified by participants are briefly described as imperative for integration in the schooling system to achieve the decolonization mission